Mechanical Design Optimization Using Advanced Optimization Techniques - Rao, R. Venkata; Savsani, Vimal J.; SpringerLink (Online service) (London : Springer London, 2012)
Mechanical design includes an optimization process in which designers always consider objectives such as strength, deflection, weight, wear, corrosion, etc. depending on the requirements. However, design optimization for a complete mechanical assembly leads to a complicated objective function with a large number of design variables. It is a good practice to apply optimization techniques for individual components or intermediate assemblies than a complete assembly. Analytical or numerical methods for calculating the extreme values of a function may perform well in many practical cases, but may fail in more complex design situations. In real design problems, the number of design parameters can be very large and their influence on the value to be optimized (the goal function) can be very complicated, having nonlinear character. In these complex cases, advanced optimization algorithms offer solutions to the problems, because they find a solution near to the global optimum within reasonable time and computational costs. Mechanical Design Optimization Using Advanced Optimization Techniques presents a comprehensive review on latest research and development trends for design optimization of mechanical elements and devices. Using examples of various mechanical elements and devices, the possibilities for design optimization with advanced optimization techniques are demonstrated. Basic and advanced concepts of traditional and advanced optimization techniques are presented, along with real case studies, results of applications of the proposed techniques, and the best optimization strategies to achieve best performance are highlighted. Furthermore, a novel advanced optimization method named teaching-learning-based optimization (TLBO) is presented in this book and this method shows better performance with less computational effort for the large scale problems. Mechanical Design Optimization Using Advanced Optimization Techniques will be useful to the industrial product designers for realizing a product as it presents new models and optimization techniques to make tasks easier, logical, efficient and effective. The book is intended for designers, practitioners, managers, institutes involved in design related projects, applied research workers, academics, and graduate students in mechanical and industrial engineering.
Introduction to Design of Mechanical Elements and Devices -- Advanced Optimization Techniques -- Applications of Existing Optimization Algorithms to the Design of Mechanical Elements -- Applications of Modified Optimization Algorithms -- Applications of Hybrid Algorithms -- Development and Applications of a New Optimization Algorithm -- Design Optimization of Heat Exchangers -- Design Optimization of Colling Towers -- Conclusions -- Algorithms and Computer Codes for the Advanced Optimization Techniques.
Keywords: Engineering; Algorithms; Engineering design; Industrial engineering; Engineering; Engineering Design; Industrial and Production Engineering; Algorithms; Computational Intelligence